The threshold effect of the Taiwan stock market on ETF under the monetary policy - Yang, Tzu-Yi (Technological and Economic Development of Economy, 2025)
Taiwan’s central bank produces tightening or easing effects by controlling the rediscount rate, which indirectly affects the stock market. An exchange-traded fund (ETF) is a fund that tracks the stock market index. ETF’s effect on trading involves not only the trading volume brought by ETF trading but also the various ETF trading strategies and the basket trading required by ETF, which makes the trading of other stocks more active. We examine whether there is a threshold effect of Taiwan’s stock market on ETF under monetary policy. The explanatory variable is the price return rate of the stock market’s weighted index; the response variable is the ETF price return rate. The rediscount rate is used as a transition variable. We analyze daily data from September 28, 2011 to September 28, 2020 using a smooth-transition autoregressive model with exogenous variables (STARX). The results reveal a threshold effect between stock market of Taiwan and ETF.First published online 18 November 2024